A Retrospective Evaluation of the Cardiometabolic Profile of Patients with COPD-Related Type 2 Respiratory Failure in the Intensive Care Unit - Oral Mentes; Deniz Celik; Murat Yildiz; Kerem Ensarioglu; Mustafa Ozgur Cirik; Tulay Tuncer Peker; Fatma Canbay; Guler Eraslan Doganay; Abdullah Kahraman (Medicina)
Background and Objectives: Chronic obstructive pulmonary disease (COPD) is a notable cause of morbidity and mortality worldwide and can become complicated by Type 2 respiratory failure. This study aimed to analyze the cardiological and metabolic comorbidities of patients admitted to the intensive care unit (ICU) due to COPD-related Type 2 respiratory failure and evaluate their effects on clinical outcomes. Materials and Methods: A retrospective analysis was conducted on 258 patients admitted to the secondary-level pulmonary disease intensive care unit between January 2022 and January 2024. Patients’ demographic data, cardiological and metabolic comorbidities, laboratory parameters, and ICU-related variables were evaluated using statistical analysis methods. Results: The most common comorbidities were hypertension (57.0%), congestive heart failure (48.1%), diabetes mellitus (31.4%), and obesity (37.6%). Female patients had significantly higher rates of hypothyroidism, hypertension, obesity, and congestive heart failure compared to males. Patients diagnosed with chronic kidney disease (CKD) had markedly higher cardiothoracic ratios and proBNP levels. ICU length of stay was considerably longer in patients with acute kidney injury (AKI) and coronary artery disease (CAD). Cardiomegaly and obstructive sleep apnea syndrome (OSAS) were more frequently observed in obese patients. Additionally, in COPD patients, a body mass index (BMI) threshold of 25.5 was determined as a cutoff value for radiological cardiomegaly findings with a sensitivity of 69.9% and a specificity of 59.5%. Elevated pCO2 and bicarbonate levels in patients receiving long-term oxygen therapy (LTOT) were associated with advanced-stage COPD. Conclusions: Metabolic and cardiological comorbidities notably impact the clinical prognosis and ICU management of patients diagnosed with COPD and Type 2 respiratory failure. This study, which aims to provide a snapshot of the comorbidities in patients requiring ICU admission due to COPD exacerbation-related Type 2 respiratory failure but without a fatal course, seeks to highlight the key areas where preventive and protective healthcare services should be focused in this patient group. Special attention should be given to monitoring female and obese patients. Future studies should explore how individualized and preventive follow-ups and treatment approaches can improve patient outcomes, with a particular emphasis on these identified areas.